2017
DOI: 10.1002/stem.2652
|View full text |Cite
|
Sign up to set email alerts
|

Common and Distinctive Functions of the Hippo Effectors Taz and Yap in Skeletal Muscle Stem Cell Function

Abstract: Hippo pathway downstream effectors Yap and Taz play key roles in cell proliferation and regeneration, regulating gene expression especially via Tead transcription factors. To investigate their role in skeletal muscle stem cells, we analyzed Taz in vivo and ex vivo in comparison with Yap. Small interfering RNA knockdown or retroviral‐mediated expression of wild‐type human or constitutively active TAZ mutants in satellite cells showed that TAZ promoted proliferation, a function shared with YAP. However, at later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
123
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(144 citation statements)
references
References 82 publications
10
123
0
Order By: Relevance
“…YAP1 and TAZ are paralogue genes which display redundant effects in terms of molecular activity but may exert divergent roles in development. 29 We also showed that the number of CD44+ cells increased after conventional chemotherapies. Their chemoresistance may involve multiple mechanisms.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…YAP1 and TAZ are paralogue genes which display redundant effects in terms of molecular activity but may exert divergent roles in development. 29 We also showed that the number of CD44+ cells increased after conventional chemotherapies. Their chemoresistance may involve multiple mechanisms.…”
Section: Discussionmentioning
confidence: 62%
“…Unlike YAP1 , TAZ was not significantly overexpressed in CD44+ cells compared to CD44− cells, although it was also associated with a reduced overall survival of nonmetastatic GC patients. YAP1 and TAZ are paralogue genes which display redundant effects in terms of molecular activity but may exert divergent roles in development …”
Section: Discussionmentioning
confidence: 99%
“…Dephosphorylation of YAP at Ser127is known to promote its nuclear translocation and its activation. 12 Thus, our results suggest that YAP could be involved in resistance exercise-induced satellite cell activation and proliferation independent of O 2 conditions. Similar results were found for TAZ targets, which were regulated by exercise but not by hypoxia, with the exception of pmp22.…”
Section: Role Of the Hippo Pathwaymentioning
confidence: 57%
“…6 Resistance training is a well-known strategy to induce skeletal muscle hypertrophy notably through protein synthesis activation, proteolysis inhibition, and activation of the myogenic program. [8][9][10][11][12][13] Although chronic hypoxia induces skeletal muscle wasting, 14 intermittent hypoxia has recently been identified as an efficient stimulus to promote satellite cell proliferation and muscle protein accretion. [8][9][10][11][12][13] Although chronic hypoxia induces skeletal muscle wasting, 14 intermittent hypoxia has recently been identified as an efficient stimulus to promote satellite cell proliferation and muscle protein accretion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation